Is it really possible for countries to simultaneously grow and reduce poverty and inequality? Going beyond global narratives. (2nd July 2020) - Cuesta, Jose; Negre, Mario; Revenga, Ana; Silva-Jauregui, Carlos
ABSTRACT: Global narratives underscore that economic growth can often coincide with reductions in poverty and inequality. However, the experiences of several countries over recent decades confirm that inequality can widen or narrow in response to policy choices and independent of economic growth. This paper analyses five country cases, Brazil, Cambodia, Mali, Peru and Tanzania. These countries are the most successful in reducing inequality and poverty while growing robustly for at least a decade since the early 2000 s. The paper assesses how good macroeconomic management, sectoral reform, the strengthening of safety nets, responses to external shocks, and initial conditions all chip away at inequality and support broad growth. Sustained and robust economic growth with strong poverty and inequality reductions are possible across very different contexts and policy choices. The comparative analysis also identifies common building blocks toward success and warns that hard-earned achievements can be easily overturned.